STUDI PROSES REVITALISASI SONGKET KUNO MINANGKABAU DI STUDIO SONGKET ERIKARIANTI - ALISA RIANDA, Dra. Zubaidah A, M.Sn, Drs. Syafwandi, M.Sn (Universitas Negeri Padang, 2013)
The aim of this research is to: 1) describe the basic concepts of Studio Songket ErikaRianti revitalization motifs, 2) describe the revitalization process of Studio Songket ErikaRianti weaving techniques, 3) describe the Studio Songket ErikaRianti dyeing process, 4) classify the Studio Songket ErikaRianti songket products of revitalization. This research is a descriptive qualitative research method. The data source of this research is, the primary data in the form of testimony from Studio Songket ErikaRianti and secondary data in the form of writing and literature reference library. Data were collected by means of observation, interviews, documentation and reference collection. Research findings that there are several stages in the process of revitalization of the ancient Minangkabau songket in the form of Studio Songket ErikaRianti revitalization motifs, techniques of weaving, dyeing process and product of revitalization.Kata kunci: process, revitalization, songket, antique, Minangkabau